2012
DOI: 10.1097/brs.0b013e31824780b8
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent-Level Range of Motion and Intradiscal Pressure After Posterior Cervical Decompression and Fixation

Abstract: For C3-C6 laminectomy, instrumentation to C7 significantly decreased flexion/extension ROM and intradiscal pressure at C6-C7 without significantly increasing either measure at C2-C3 or C7-T1 relative to C3-C6 fixation. In the setting of a C3-C7 laminectomy, when instrumenting to either C2 or T2, consideration should be given to including both levels within these constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…However, biomechanical and clinical studies suggested that adjacent-level kinematic might predispose to adjacent-level degeneration after ACF. [3,4] Degenerative changes in adjacent-level and unsatisfactory clinical outcomes were documented. [5,6] Adjacent segment diseases (ASDs), whether representing an enhanced degeneration due to adjacent fusions or merely the natural progression of degeneration, have been recognized as an important entity after ACF.…”
Section: Introductionmentioning
confidence: 99%
“…However, biomechanical and clinical studies suggested that adjacent-level kinematic might predispose to adjacent-level degeneration after ACF. [3,4] Degenerative changes in adjacent-level and unsatisfactory clinical outcomes were documented. [5,6] Adjacent segment diseases (ASDs), whether representing an enhanced degeneration due to adjacent fusions or merely the natural progression of degeneration, have been recognized as an important entity after ACF.…”
Section: Introductionmentioning
confidence: 99%
“…The development of adjacent segment degeneration (ASD) following anterior cervical decompression and fusion (ACDF) is well reported in the literature [4][5][6][7][8][9][10][11][12][13][14][15]. Within the past few decades, both in vivo and in vitro biomechanical evidence suggest that arthrodesis may augment stress on the unfused adjacent levels [16][17][18][19][20][21]. Hilibrand et al [7] reported an annualized incidence of 2.9 % per year for developing symptomatic ASD after singlelevel ACDF and estimated that about 25.6 % of patients would have symptomatic ASD within 10 years of their index surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The flexion and extension responses of this model were compared with previous cadaveric studies reported by Nightingale et al [5] and Wheeldon et al [6]. In addition, the inter-vertebral disc pressures(IDP) were compared to 2Nm flexion/extension quasi-static experiment in C2-C3, C6-C7 segments reported by Dmitriev [7] and the 5Nm axial rotation and lateral bending quasi-static experiment in C4-C5, C5-C6 segments reported by Kretzer [8].…”
Section: Figure 1 the Head-neck Model In Cartesian Coordinate Systemmentioning
confidence: 99%